2013
DOI: 10.1364/oe.21.030653
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric velocity measurements through a fluctuating gas-liquid interface employing adaptive optics

Abstract: Optical transmission through fluctuating interfaces of mediums with different refractive indexes is limited by the occurring distortions. Temporal fluctuations of such distortions deteriorate optical measurements. In order to overcome this shortcoming we propose the use of adaptive optics. For the first time, an interferometric velocity measurement technique with embedded adaptive optics is presented for flow velocity measurements through a fluctuating air-water interface. A low order distortion correction tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…A previous experimental analysis revealed that low-order Taylor series orders, respectively Zernike polynomials (piston/stroke, tip/tilt and defocus) dominate the wavefront distortions [12]. Distortions of higher orders, i.e., with higher spatial frequency can be neglected at the considered flow measurement task.…”
Section: (A) Tilt δX In X-direction (Tip): On One Side a Displacementmentioning
confidence: 96%
See 4 more Smart Citations
“…A previous experimental analysis revealed that low-order Taylor series orders, respectively Zernike polynomials (piston/stroke, tip/tilt and defocus) dominate the wavefront distortions [12]. Distortions of higher orders, i.e., with higher spatial frequency can be neglected at the considered flow measurement task.…”
Section: (A) Tilt δX In X-direction (Tip): On One Side a Displacementmentioning
confidence: 96%
“…In general, several optical modulators are available for the correction of wavefront distortions, e.g., deformable membrane mirrors, micro-electro-mechanic-system (MEMS) mirror arrays and liquid-crystal spatial light modulators. In our former research work [11,12] we have employed a deformable membrane mirror exhibiting 17 electrostatic actuator elements and built-in piezoelectric tip-tilt unit. An obstacle of the deformable membrane mirror was its restricted defocus range due to the limited curvature of the membrane.…”
Section: (A) Tilt δX In X-direction (Tip): On One Side a Displacementmentioning
confidence: 99%
See 3 more Smart Citations